Antibody Micropatterned Lubricant‐Infused Biosensors Enable Sub‐Picogram Immunofluorescence Detection of Interleukin 6 in Human Whole Plasma. Issue 45 (20th October 2020) - Shakeri, Amid; Jarad, Noor Abu; Terryberry, Jeff; Khan, Shadman; Leung, Ashlyn; Chen, Simeng; Didar, Tohid F.
Abstract: Recent studies have shown a correlation between elevated interleukin 6 (IL‐6) concentrations and the risk of respiratory failure in COVID‐19 patients. Therefore, detection of IL‐6 at low concentrations permits early diagnosis of worst‐case outcome in viral respiratory infections. Here, a versatile biointerface is presented that eliminates nonspecific adhesion and thus enables immunofluorescence detection of IL‐6 in whole human plasma or whole human blood during coagulation, down to a limit of detection of 0.5 pg mL −1 . The sensitivity of the developed lubricant‐infused biosensor for immunofluorescence assays in detecting low molecular weight proteins such as IL‐6 is facilitated by i) producing a bioink in which the capture antibody is functionalized by an epoxy‐based silane for covalent linkage to the fluorosilanized surface and ii) suppressing nonspecific adhesion by patterning the developed bioink into a lubricant‐infused coating. The developed biosensor addresses one of the major challenges for biosensing in complex fluids, namely nonspecific adhesion, therefore paving the way for highly sensitive biosensing in complex fluids. Abstract : This paper presents an ultrasensitive biosensor for detecting interleukin 6 in human plasma with a limit of detection of 0.5 pg mL −1 . This outstanding performance is achieved by covalently patterning of an IL‐6 detection bioink into a lubricant‐infused surface enabling highly sensitive immunofluorescence detection of IL‐6, which is also an important marker for monitoring respiratory failure in Covid‐19 patients.